Konsepsi Dakwah Islamiyah dalam Konteks Konservasi Alam dan Lingkungan - Erwin Jusuf Thaib (Al-Ulum, 2011)
Currently, Islamic preaching seems mostly dealing with the problems of Muslims’ prays and rituals. Whereas, the problem faced by most Muslims today are more complicated if this fact is explored farther. Therefore, the need for an alternative preaching (dakwah) to tackle the environmental degaradation is crutial. Based on this fact, Islamic reaching is expected to be able to be an alternative medium to alert Muslim about how important the natural conservation and environmental preservation are. It becomes a manifestation of the human leadership (khalifah) and a quarantee of human’s life in this world.